Plundering the Skilled Workforce: Depriving Developing Nations of Their Most Valuable Assets - Hasan Gürak (World Review of Political Economy)
Whether developed or less developed, all countries need skilled mental labor (SML) to use technologies effectively and to attain economic growth and development. Without appropriate SML, no country can make the best use of its firms and institutions. Time and investment are required for an individual to become a skilled mental laborer, but these are not sufficient. The training must be at a level where contemporary technologies can be used effectively, so that the highest benefit can be given to society and companies. The most disturbing aspect of the issue is that although there are very few skilled mental laborers who are educated and equipped with modern qualifications, they generally migrate to more developed and richer countries to achieve better living conditions. Developed countries have found an excuse for this kind of migration by saying “We need skilled mental laborers.” The pertinent critical questions are as follows. While it is acknowledged that developed countries require SML, what about less developed countries? Do they not also have a need for SML? The crucial and vital question is which countries have a greater need for SML, developed countries or less developed countries?